The Effect of Cloud-Based Supply Chain Integration and Information Security Initiatives on Supply Chain Robustness and Performance - Rani Mahita Aji; Triwulandari Satitidjati Dewayana (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
The purpose of this research is to examine the relationship among cloud-based supply chain integration, information security initiatives, supply chain robustness and supply chain performance. This research gathered from 132 respondents, professional workers of seven telecommunication service provider companies in Indonesia located in the capital city of Jakarta. The study used an online questionnaire with a Likert scale of 1-5. PLS-SEM method is used to test relationship between variables with SmartPLS software version 3.0. The results show that cloud-based supply chain integration and information security initiatives have a positive and significant effect on supply chain robustness, supply chain robustness also has a positive and significant effect on the supply chain performance. In addition, cloud-based supply chain integration and security initiatives have a positive and significant impact on supply chain performance through the mediation of supply chain robustness. This research shows that companies can take opportunities to improve supply chains through the application of cloud technology in supply system integration, but still need to improve supply information security initiative in order to create a robust supply chain against various threats, disruptions, and disasters.